PENGARUH HARGA DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PELANGGAN GOOMA TEA BAR MAL KELAPA GADING DI JAKARTA UTARA - Rita Eka Setianingsih; Liaw BunFa; Abdulah Rakhman; Ari Hadi Prasetyo (Sekolah Tinggi Pariwisata Mataram, 2022)
Contemporary drinks are very popular with the people of Indonesia, even the whole world. Drinks made from coffee, cheese tea, and boba are very popular with the public so that many companies have sprung up to make beverage businesses. One of the companies participating in the industry is GOOMA. Many companies follow the trend of bubble tea, cheese tea, and coffee, but GOOMA doesn't want to follow the trend. GOOMA wants to bring and educate matcha to people in Indonesia. The theory used in this research is the theory of price, brand image, and purchasing decisions. The object of this research is the customer of GOOMA Tea Bar at Kelapa Gading Mall. Sampling in this study used probability sampling with simple random sampling technique. The method of data collection in this study used a questionnaire. Data analysis techniques in this study are descriptive analysis, classical assumption test, and multiple linear regression analysis. The research data was processed using SPSS 20. The results showed that price had a positive effect on customer purchasing decisions at GOOMA Tea Bar Mal Kelapa Gading and, brand image had a positive effect on customer purchasing decisions at GOOMA Tea Bar Mal Kelapa Gading.